2006
DOI: 10.1245/aso.2006.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features Associated With Having Four or More Metastatic Axillary Nodes in Breast Cancer Patients With a Positive Sentinel Lymph Node

Abstract: Background:The survival benefit of a completion axillary lymph node dissection (ALND) in patients after removal of a metastatic sentinel lymph node (SLN) is uncertain and is under study in ongoing clinical trials. The completion ALND remains necessary, however, for the identification of cases with at least four metastatic lymph nodes, in which extended-field locoregional and/or postmastectomy radiation will be recommended. Our goal was evaluate clinicopathologic features that might serve as surrogates for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 24 publications
6
30
1
Order By: Relevance
“…Breast lesions exceeding 2 cm in size have been reported to be predictors of a high number of lymph node metastases. 16 In this study, however, the size of breast lesions was similar between the 2 groups at a median of less than 2 cm. Since more than 50% of tumours were T1 stage, the size of the tumour did not appear to influence the type of surgery.…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…Breast lesions exceeding 2 cm in size have been reported to be predictors of a high number of lymph node metastases. 16 In this study, however, the size of breast lesions was similar between the 2 groups at a median of less than 2 cm. Since more than 50% of tumours were T1 stage, the size of the tumour did not appear to influence the type of surgery.…”
contrasting
confidence: 46%
“…Since the total number of nodes removed on CALND was expected to be higher than that in SLNB, we did not perform a statistical comparison. However, a higher percentage of positive SLNs was strongly predictive of further CALND, a course of action supported by the literature, which shows a higher percentage of positive SLNs to be predictive of higher likelihood of axillary lymph node (ALN) involvement 16 as well as decreased survival. 17 Interestingly, the size of metastasis in the largest node was not a predictor of further CALND, but having microscopic disease made it less likely for a patient to undergo further CALND.…”
Section: Discussionmentioning
confidence: 60%
“…17 In our study we found the same results. Bols ter et al and Co u fal et al sta ted that the in ciden ce of n-SLN me tas ta ses was re la ted to the si ze of the SLN me tas ta ses.…”
Section: Discussionsupporting
confidence: 87%
“…Six studies only focused on predictive factors for having at least 4 positive axillary nodes [70][71][72][73][74][75]. Seven studies only evaluated patients with SLN micrometastases [8;76-81].…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Potentially appropriate references to be included in review, n= 64 Predictive factors in SLN micromets, n= 7 excluded [5,[75][76][77][78][79][80] References retrieved for more detailed evaluation, n= 85 Predictive factors for ≥ 4 positive axillary nodes, n= 6 excluded [69][70][71][72][73][74] No SLN performed, only predictive factors of positive ALND, n= 17 excluded [4,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] References with usable information, n= 56 -SNB performed -completion ALND in SLN+ cases -data on predictive factors for positive NSN Meta-analysis, n= 1 excluded [87] No raw data, n= 4 excluded [13,20,81,82] Overlap of data between studies, n= 5 excluded [11,22,23,88,89] SLN positive with CK-IHC only, n= 2 excluded [83][84] Only tumours < 15 mm, n= 1 excluded [86] Only special types of breast cancer, n=1 excluded …”
mentioning
confidence: 99%